Work Stress Overview in Midwives during the Covid-19 Pandemic - Maria Wendelina Dian Salombre; Apris A Adu; Honey Ivone Ndoen (Journal of Health and Behavioral Science, 2022)
Job stress is the interaction between the characteristics of workers and the conditions of the work environment that threaten individuals that cannot be matched by their abilities, causing negative impacts on physical, psychological, and behavior. Midwives are one of the health workers who serve patients during the Covid-19 pandemic. The increase in the number of patients in the obstetrics room, both positive for Covid -19 and not, makes midwives often feel anxious, tired, afraid, and even worried about being exposed to the Covid-19 virus, which is undoubtedly one of the factors that can cause work stress for midwives. The aim is to determine the description of work stress based on physiological, psychological, and behavioral symptoms in the midwifery room. The population was all midwives in the midwifery room, namely 43 people with a sample of 39. The results showed that the prevalence of work stress levels in midwives in the midwifery room was 26 people (66.7%) experiencing moderate work stress.Moreover, of respondents who experience work stress based on psychological symptoms, 82.1% are in the moderate category. Work stress based on Physiological symptoms as much as 100% is in the medium category, and work stress based on behavioral symptoms as much as 62.9% is in the high category. This research shows that applying individual strategies and stress management can reduce and prevent workplace stress.